Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

When solving a trigonometric limit such as:

$$\lim_{x \to 0} \frac{\sin(5x)}{\sin(4x)}$$

we rework the equation to an equivalent for to fit the limit of sine "rule":

$$\lim_{x \to 0}\frac{\sin(x)}{x}=1$$

so, we move forward in such a manner as follows:

$$=\lim_{x \to 0} \frac{\frac{5\sin(5x)}{5x}}{\frac{4\sin(4x)}{4x}}$$

$$=\frac{5}{4}\lim_{x \to 0} \frac{\frac{\sin(5x)}{5x}}{\frac{\sin(4x)}{4x}}$$

$$=\frac{5}{4}\cdot\frac{1}{1}$$ $$L=\frac{5}{4}$$

From that mindset, I am trying to find this trigonometric limit:

$$\lim_{x\to 2} \frac{\cos(x-2)-1}{x^{2}+x-6}$$

I know the Limit "rule" for cosine is:

$$\lim_{x\to 0} \frac{\cos(x)-1}{x}=0$$

If you use direct substitution in the original function you end up with an equation that is same in value to the rule presented. So, from that I am assuming that the answer is $0$. I am just trying to prove that in a step-by-step manner as I did with the sine limit.

P.S. I searched through many many pages of questions and didn't find something that helped. So, if I am repeating a question, I apologize that I missed it.

Thanks for the help!

share|cite|improve this question
up vote 3 down vote accepted

If you factor the denominator you would get:

$$\lim_{x\to 2} \frac{\cos(x-2)-1}{x^{2}+x-6}=\lim_{x\to 2} \frac{\cos(x-2)-1}{x-2}\frac{1}{x+3}=\ldots$$

share|cite|improve this answer
wow. I feel like a moron now. apparently i need a break if I didn't see that. Thanks! I'll accept your answer as soon as it allows. – PathemaMike Jul 2 '14 at 0:07
@PathemaMike When you plug in $x=2$ and you find that the denominator is equal to $0$, you'll immediately understand that $2$ is a root of $x^2+x-6$, so we can write it as $(x-2)(x-\alpha)$. And we note that we have $\cos(x-2) $, so we could write it as our general limit. Hope this clarifies things for you. ;-) – Hakim Jul 2 '14 at 0:10
Thanks! I think I just need to step away for a minute, and let my mind do other things if I didn't see such an obvious solution! – PathemaMike Jul 2 '14 at 0:16
@PathemaMike You're welcome! $\overset{\cdot\cdot}\smile$ – Hakim Jul 2 '14 at 0:39

For an easy evaluation you can use La'Hospital's rule. $$ \lim_{x\to 2}\frac{\cos(x-2)-1}{x^2+x-6} = \lim_{x\to 2}\frac{-\sin(x-2)}{2x+1}=0 $$

share|cite|improve this answer
This site uses MathJax. – choco_addicted Apr 23 at 8:29

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.